2006
DOI: 10.1182/blood-2006-05-024109
|View full text |Cite
|
Sign up to set email alerts
|

Hodgkin lymphoma and immunodeficiency in persons with HIV/AIDS

Abstract: In persons with HIV/AIDS (PWHAs), Hodgkin lymphoma (HL) risk is increased. However, HL incidence in PWHAs has unexpectedly increased since highly active antiretroviral therapy (HAART) was introduced. We linked nationwide HIV/AIDS and cancer registry data from 1980 through 2002. Immunity was assessed by CD4 T-lymphocyte counts at AIDS onset. Annual HL incidence rates were calculated for 4 through 27 months after AIDS onset. IntroductionHodgkin lymphoma (HL) risk is significantly increased in persons with HIV/A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
308
3
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(340 citation statements)
references
References 35 publications
20
308
3
9
Order By: Relevance
“…Some studies support our results. 21,38 Biggar et al found that the incidence of HL is highest at moderate CD4 counts (150-199 cells/mm 3 ), 38 and another study 39 found that the risk of HL increased for CD4 counts of <350 cells/mm 3 and peaked at 50 to 99 cells/mm 3 . We found a linear relationship between with decreasing CD4 count and increasing incidence of HL.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies support our results. 21,38 Biggar et al found that the incidence of HL is highest at moderate CD4 counts (150-199 cells/mm 3 ), 38 and another study 39 found that the risk of HL increased for CD4 counts of <350 cells/mm 3 and peaked at 50 to 99 cells/mm 3 . We found a linear relationship between with decreasing CD4 count and increasing incidence of HL.…”
Section: Discussionmentioning
confidence: 98%
“…Despite this being the second most common cancer in Africa incidence remains small when in contrast to the 5-25-fold risk observed in western populations [26], [27] and [28]. Even so, none of the other tumour types examined being oral, liver or stomach cancer, melanoma, leukaemias or sarcomas showed a similar increased risk [25].…”
Section: Epidemiologymentioning
confidence: 99%
“…Immune reconstitution with cART is causing an increased risk for these tumours by shifting HIV-infected individuals to a level of immunosuppression associated with highest risk [27] and [28]. The Reed Sternberg (RS) cell seems to play a central role in facilitating such complex interactions.…”
Section: Immunbiology Histological Subtype and Viral Coinfectionmentioning
confidence: 99%
“…However, classical Hodgkin lymphoma is observed more frequently 1 and HIV patients have a 9.4-fold increased risk of developing classical Hodgkin lymphoma compared with the general population. 2,3 Although HIV-related classical Hodgkin lymphoma occurs at any CD4 blood count, it is most frequently observed in patients with a moderate immune deficiency and CD4 blood counts of 150-249 cells/ml. 2,4 As Hodgkin-and Reed-Sternberg cells, the tumor cells in classical Hodgkin lymphoma, usually constitute a small subpopulation of the cells in affected lymph nodes; it is likely that the microenvironment, largely composed of CD4 ĂŸ T regulatory 1 cells, has an essential role in the pathophysiology of the disease.…”
mentioning
confidence: 99%
“…2,3 Although HIV-related classical Hodgkin lymphoma occurs at any CD4 blood count, it is most frequently observed in patients with a moderate immune deficiency and CD4 blood counts of 150-249 cells/ml. 2,4 As Hodgkin-and Reed-Sternberg cells, the tumor cells in classical Hodgkin lymphoma, usually constitute a small subpopulation of the cells in affected lymph nodes; it is likely that the microenvironment, largely composed of CD4 ĂŸ T regulatory 1 cells, has an essential role in the pathophysiology of the disease. 5 As HIV infection usually involves decreased CD4 ĂŸ T-cell counts in the peripheral blood, several studies have addressed the issue of the microenvironment in HIV-associated Hodgkin lymphoma and have found the CD4/CD8 T-cell ratio to be inverted.…”
mentioning
confidence: 99%